HUBUNGAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN PERILAKU KEAGAMAAN SISWA KELAS XI SMA AL-RIFA’IE KETAWANG GONDANGLEGI MALANG - Haifa Ayu Choiriani; Ika Ratih Sulistiani; Yorita Febry Lismanda (VICRATINA, 2019)
This study discusses the relationship between learning achievement of Islamic Education with religious behavior of class XI of SMA Al-Rifa'ie Ketawang Gondanglegi Malang by making some of its students the object of research. This research is motivated by the formulation of the problem of whether there is a relationship between the learning achievement of Islamic Education and the religious behavior of class XI Al-Rifa'ie High School students. These problems are discussed through quantitative research. This research was conducted in the XI IPA class of Al-Rifa'ie High School. In this study the data collection process was obtained by questionnaire, and observation. Data were analyzed using the product moment statistical formula approach. This study shows that there is a relationship that is considered sufficient between the learning achievements of Islamic Education and the religious behavior of students. This can be evidenced by the results of research which stated that there were 21 students and 11 students in the high religious performance and behavior categories. In addition, it is also proven through the person product moment formula which states the magnitude of the correlation coefficient (r count) is 0.349 compared to the r table, which is 0.344 with a significant error rate of 5%. Then the conclusion is there is a positive relationship between learning achievement of Islamic Education with religious behavior in the same class XI IPA Al-Rifa'ie Ketawang Gondanglegi Malang. Keywords: Learning Achievement and Diversity Behavior